Complement inhibitor factor H expressed by breast cancer cells differentiates CD14+ human monocytes into immunosuppressive macrophages. (1st January 2020) - Smolag, Karolina I.; Mueni, Christine M.; Leandersson, Karin; Jirström, Karin; Hagerling, Catharina; Mörgelin, Matthias; Barlow, Paul N.; Martin, Myriam; Blom, Anna M.
ABSTRACT: Macrophages are a major immune cell type in the tumor microenvironment, where they display a tumor-supporting phenotype. Factor H (FH) is a complement inhibitor that also plays a role in several cellular functions. To date, the phenotype of monocytes stimulated with FH has been unexplored. We discovered that FH is a survival factor for CD14 + primary human monocytes, promoting their differentiation into macrophages in serum-free medium. This activity was localized to the C-terminal domains of FH and it was inhibited in plasma, indicating that the phenomenon may be most relevant in tissues. FH-induced macrophages display characteristics of immunosuppressive cells including expression of CD163 and CD206, release of the anti-inflammatory cytokine IL-10 and changes in metabolism. Furthermore, FH-induced macrophages express low levels of HLA-DR but high levels of co-inhibitory molecule programmed death-ligand 1 (PD-L1), and accordingly, a reduced capacity for T-cell activation. Finally, we show that FH is expressed by human breast cancer cells and that this correlates with the presence of immunosuppressive macrophages, breast cancer recurrence and severity of the disease. We propose that the expression of FH by tumor cells and the promotion of an immunosuppressive cancer microenvironment by this protein should be taken into account when considering the effectiveness of immunotherapies against breast cancer.